Carbon–Phosphorus Coupling Governs Microbial Effects on Nutrient Acquisition Strategies by Four Crops - Zhang, Deshan; Zhang, Yuqiang; Zhao, Zheng; Xu, Sixin; Cai, Shumei; Zhu, Haitao; Rengel, Zed; Kuzyakov, Yakov (Frontiers in Plant Science, 2022)
Plants adjust root morphological and/or exudation traits in response to phosphorus (P) mobilization mediated by microorganisms. We hypothesized that straw application coupled with P fertilization would influence microbial P and then root nutrient-acquisition strategies related to crop growth. Root morphological (length and average diameter) and exudation traits (acid phosphatase and carboxylates) of Brassica chinensis, Solanum lycopersicum, Lactuca sativa, and Vigna unguiculata in response to microbial P dynamics were characterized in no-P and P-fertilized soil with/without straw addition. Straw addition increased the growth of fungi and bacteria, stimulating microbial P immobilization at day 24. The high microbial abundance was associated with four tested crops having short roots in straw-amended compared with no-straw soil at day 24. In straw-amended soil, B. chinensis and S. lycopersicum shifted toward root P-acquisition strategies based on fast elongation and strong carboxylate exudation from days 24 to 40. Such effective root P-acquisition strategies together with microbial P release increased shoot P content in S. lycopersicum in straw-amended compared with those without straw at day 40. Conversely, L. sativa and V. unguiculata produced short roots in response to the stable (or even increased) microbial P after straw addition till day 40. In straw-amended soil, high P application stimulated root elongation and carboxylate exudation in L. sativa and V. unguiculata, whereas carboxylate exudation by S. lycopersicum was decreased compared with the straw-amended but non-fertilized treatment at day 40. In summary, root P-acquisition strategies in response to microbial P differed among the tested crop species. Phosphorus fertilization needs to be highlighted when returning straw to enhance P-use efficiency in vegetable cropping systems.